O Trabalho e as Migrações na Envolvente da Companhia de Fiação e Tecidos de Guimarães: Operários, Camponeses e “Vendeiros” - Rei, Mariana (Trabalhos de Antropologia e Etnologia, 2020)
In this paper, I try to understand how fixation and geographic mobility, as well as specialization and professional adaptability, are articulated as ways to "improve life" in the surroundings of an old textile factory in the municipality of Guimarães. Given the complexity of the family and labour relations that emerge here, I aim at questioning how the strategies adopted in their professional and migratory trajectories accompany the diversity of family and class situations at the local level. Considering that this is a context of diffuse industrialization, I will attend especially to the comparisons with the peasantry, in terms of continuities and changes with the workingclass world.